2017
DOI: 10.1038/srep46700
|View full text |Cite
|
Sign up to set email alerts
|

Imaging genetics approach to Parkinson’s disease and its correlation with clinical score

Abstract: Parkinson’s disease (PD) is a progressive neurodegenerative disorder associated with both underlying genetic factors and neuroimaging findings. Existing neuroimaging studies related to the genome in PD have mostly focused on certain candidate genes. The aim of our study was to construct a linear regression model using both genetic and neuroimaging features to better predict clinical scores compared to conventional approaches. We obtained neuroimaging and DNA genotyping data from a research database. Connectivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Such findings are in contrast with those of previous studies in which imaging was a predictor of long-term motor outcomes and, when based on the same PPMI data, imaging in combination with genetics was used to predict MDS-UPDRS scores. 6,7 …”
mentioning
confidence: 99%
“…Such findings are in contrast with those of previous studies in which imaging was a predictor of long-term motor outcomes and, when based on the same PPMI data, imaging in combination with genetics was used to predict MDS-UPDRS scores. 6,7 …”
mentioning
confidence: 99%
“…Our study considered two types of information (i.e., neuroimaging and genetic information) and many procedures are necessary to process them. The schematic of the overall processing steps is given in Fig 1 [24]. Details regarding the procedures are provided later in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The ENIGMA protocol included the following processes: 1) call rate check per subject, 2) sex check, 3) sibling pair identification and 4) population stratification using multi-dimensional scaling. In addition, the SNPs that did not meet the quality control criteria (minor allele frequency < 0.01; genotype call rate < 95%; Hardy-Weinberg equilibrium < 10 −6 ) were filtered out of the dataset [24,28,29]. SNPs were only kept if they did not belong to the Caucasian population according to the HapMap3 reference population.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the success in characterizing complex neurodegenerative diseases, such as AD, imaging genetics analyses have been scarcely applied on PD. However, studies combining neuroimaging and genomic data have been shown effective in discovering potential genetic drivers of PD [10,11]. Kim and coworkers investigated the factors underlying the Movement Disorder Society-sponsored unified Parkinson's disease rating scale (MDS-UPDRS) scores in PD patients [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies combining neuroimaging and genomic data have been shown effective in discovering potential genetic drivers of PD [10,11]. Kim and coworkers investigated the factors underlying the Movement Disorder Society-sponsored unified Parkinson's disease rating scale (MDS-UPDRS) scores in PD patients [10]. The authors showed that linear models trained on genetic and neuroimaging data improve predictions on MDS-UPDRS scores, suggesting that genomic and brain imaging data provide complementary information in PD.…”
Section: Introductionmentioning
confidence: 99%